Towards a Critical Decolonial Turn/Theory: Beyond the Binary of the West Versus Africa - Richard Fosu (Africa Spectrum)
As writing on decolonisation in African Studies has surged, efforts to avoid the concept becoming a mere metaphor, bandwagon, ideological trope, or mantra have grown, with scholars emphasising decolonial theory's ongoing relevance to the emancipation of formerly colonised Africans. This essay argues that to achieve its emancipatory goals, decolonial theory and intended praxes must re-centre the everyday realities of African societies. Recentring Africans is needed to move beyond Global North versus Africa as the ontological site for decolonisation. Recentring African societies has important epistemological and methodological implications for recentring African agency to make the decolonial project less reactionary and more proactive. I propose “post-independence” as an approach to decolonisation that offers descriptive and prescriptive means to locate the (im)material responsibilities of Africans in recentring their history. Post-independence allows a reimagining of how to undo the effects of colonialism by presenting colonialism as an episodic moment in Africa's long history.